2012
DOI: 10.2340/00015555-1283
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Reduces the Occurrence of Cerebrovascular Events among Taiwanese Psoriatic Patients: A Nationwide Population-based Study

Abstract: Psoriasis is a chronic inflammatory disease. The aim of this study was to evaluate the effects of methotrexate and retinoid on risks for developing cerebrovascular disease among psoriatic patients. A population-based nested case-control study was conducted using the Taiwanese National Health Insurance database. Cox proportional hazards models were adopted. The hazard ratio (HR) of newly developed cerebrovascular disease was 1.28 (95% confidence interval (CI) = 1.162-1.413; p < 0.0001) for psoriatic vs. non-pso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…Randomized controlled trials (RCT) of TNFi in psoriasis and PsA have not shown significant differences in risk of CV events although timespans of these studies have been short 47,48,49,50 . Randomized controlled trials (RCT) of TNFi in psoriasis and PsA have not shown significant differences in risk of CV events although timespans of these studies have been short 47,48,49,50 .…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Randomized controlled trials (RCT) of TNFi in psoriasis and PsA have not shown significant differences in risk of CV events although timespans of these studies have been short 47,48,49,50 . Randomized controlled trials (RCT) of TNFi in psoriasis and PsA have not shown significant differences in risk of CV events although timespans of these studies have been short 47,48,49,50 .…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…As aforementioned, psoriasis is associated with higher occurrences of metabolic syndrome [1]. Of particular interest is the association between psoriasis and diabetes.…”
Section: Introductionmentioning
confidence: 98%
“…Psoriasis is an inflammatory skin condition affecting approximately 0.2-3% of the world's population with variations among different ethnic groups [1,2]. The etiology of the disease is still not clear, but both genetic and environmental factors are believed to play a role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As psoriasis is recognized as a systemic inflammatory disorder, it is reasonable to hypothesize that certain amount of anti‐inflammation or immune‐suppression may be beneficial for ameliorating disease progression. In fact, methotrexate therapy has been shown to reduce the incidence of vascular disease in patients with psoriasis and rheumatoid arthritis 15,16 . Therefore, the current study also explored if methotrexate treatment modulates the risk of severe vascular events in psoriatic patients when the temporal relationship between onset of psoriasis and metabolic disorder is taken into consideration.…”
Section: Introductionmentioning
confidence: 99%